Diacylglyceryl-N,N,N-trimethylhomoserine-dependent lipid remodeling in a green alga, Chlorella kessleri - Yutaro Oishi; Rie Otaki; Yukari Iijima; Eri Kumagai; Motohide Aoki; Mikio Tsuzuki; Shoko Fujiwara; Norihiro Sato (Communications Biology, 2022)
Oishi et al. report that the synthesis of a betaine lipid, diacylglyceryl-N,N,N-trimethylhomoserine (DGTS) in a green alga Chlorella kessleri replaces phosphatidylcholine and phosphatidylethanolamine, the two most abundant phospholipids, during phosphate deprivation. This study provides insights into the understanding of the phosphorus-deficiency acclimation strategies via lipid remodeling in lower green plants.